Fabrication of multi-walled carbon-nanotube-grafted polyvinyl-chloride composites with high solar-thermal-conversion performance. (20th January 2019) - Shen, Xiaoning; Ji, Minzun; Zhang, Shiming; Qin, Yujun; Zhang, Pu; Wang, Yapei; Guo, Zhi-Xin; Pan, Mingwang; Zhang, Zuoqi
Abstract: The optical absorption properties of carbon nanotubes (CNTs) have attracted extensive research attention. Here we report the fabrication of sea-island structured polymer-based multi-walled CNT (MWNT) composite with high solar-thermal-conversion performance. MWNT-grafted 4-chloromethyl styrene (MWNTs-g-CMS) is prepared via esterification between carboxyl groups on the MWNT surface and the chloromethyl group of the CMS in the presence of a phase-transfer reagent in water. Covalent bonding between the CMS and the MWNTs is confirmed by Fourier transform infrared spectra. Thermogravimetric analysis of the MWNTs-g-CMS shows a mass percentage of the attached methyl styrene chains as high as 24.31 wt%. Subsequently, polymer-based MWNT- graft -polyvinyl-chloride (MWNTs- g -PVC) composite was prepared via an in-situ graft polymerization between the vinyl chloride and active styryl groups of the MWNTs-g-CMS. The MWNT grafting efficiencies in a series of MWNTs-g-PVC composites are 0.013–0.103%. The sea-island structure of the MWNTs-g-PVC composites and the fine dispersion of MWNTs in the island are verified by electron microscopy. The solar-thermal conversion performance of the MWNTs-g-PVC composites is studied. The composites exhibit excellent light-absorption properties that resemble a black body, and yield a higher solar-thermal conversion efficiency than the carboxylic MWNT (PVC/MWNTs-COOH) composites, which is attributed to the sea-island structure and the good dispersion of MWNTs in the islands.